The evaluation of prothrombin time and activated partial thromboplastin time among diabetic and healthy controls in Africa: systematic review and meta-analysis - Getu, Fasil; Alemayehu, Ermiyas; Tesfaye, Addisu; Genanew, Birhanu; Walle, Muluken (Frontiers in Medicine, 2024)
Introduction: DM is characterized by chronic hyperglycemia resulting from defects in insulin secretion or action. DM patients have a disturbance of hemostasis, leading to a prothrombotic state characterized by platelet hypersensitivity, coagulation factor disorders, and hypo-fibrinolysis. The primary goal of this systematic review and meta-analysis was to determine the pooled SMD of PT and APTT of DM patients in Africa. This systematic review and meta-analysis was conducted based on the guidelines of the PRISMA. PubMed, Google Scholar, Science Direct, Dove Press, Cochrane Online, and African journals online were searched systematically. The qualities of the included studies were assessed by two independent reviewers using the JBI critical appraisal tools. Data were extracted in an Excel sheet and then exported to STATA version 11 for analysis. A Random-effect model was fitted to estimate the pooled SMD and Higgins I-square test statistics were done to test the heterogeneity of studies. .The pooled SMD of PT among DM patients in Africa was -0.18, (95% CI: -0.72, 0.36).The pooled SMD of APTT among DM patients in Africa was -0.48, (95% CI: -1.18, 0.21). There was no statistically significant difference in the SMD of PT and APTT among DM patients in Africa compared to healthy controls. The pooled SMD of APTT among Type 1 DM patients in Africa was 0.86 (95% CI: 0.04, 1.69) whereas the SMD among Type 2 DM was -0.42 (95% CI: -1.24, 0.40). The SMD of APTT in Type 1 DM and controls showed a statistically significant difference compared with Type 2 DM and controls (p=0.041). The SMD of APTT in Africa that is determined using a case-control study design showed a statistically significant difference compared to the SMD that is determined using a comparative cross-sectional study design. Even though different studies conducted across African countries showed the presence of coagulation abnormality in DM, this systematic review and meta analysis revealed that there is no statistically significant SMD of PT and APTT in DM patients compared to controls. However it is recommended that physicians routinely check APTT levels in Type I DM patients in order to evaluate coagulation status